PENGARUH MODUL KESETIMBANGAN KIMIA BERBASIS INKUIRI TERSTRUKTUR DENGAN TIGA LEVEL REPRESENTASI TERHADAP MODEL MENTAL SISWA - Nurhasanah Nurhasanah; Minda Azhar; Alizar Alizar (Jurnal Tadris Kimiya, 2022)
Students find it difficult to understand the material of chemical equilibrium. One of the efforts to overcome these student difficulties is to use a structured inquiry-based module equipped with three levels of representation. This study aims to determine the effect of using the module on students' mental models. This study used a posttest-only control design conducted in two schools. In the design, each school had two groups, namely the experimental group and the control group. The two-tier diagnostic test instrument was used to test the mental models of 134 students. The hypothesis was tested by ttest using the SPSS 16.0 program. The results of the ttest for each school were 0.011 at SMAN 3 Padang and 0.008 at SMAN 13 Padang, with a 0.05 significance level. The results of the t-test showed that the use of the module affected students' mental models.